STUDI AKSI KORPORASI TERHADAP RETURN SAHAM - Sululing, Siswadi; Syarifuddin Rasyid; Aini Indrijawati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to prove the effect of the stock split variable and the warrants variable on the stock returns of companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The researcher uses secondary data, namely documentation data in the form of company corporate actions: stock splits and warrants. The data were analyzed using multiple linear regression analysis method, and assisted by SPSS 24 data processing tools. The results showed that the stock split variable had no effect on stock returns, as well as the warrants variable had no effect on stock returns.